Sosialisasi Pelestarian Lingkungan di Dukuh Plalan Desa Kadokan - Dwi Nurwanti, Yulian; Putri, Tasya; Aziz Zaelani, Muhammad; Dewi, Nourma; Nurramadani, Ardan (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2024)
Environmental conservation has the connotation that the environment must be maintained as it is. while the environment is actually used within the framework of development, this means that the environment is undergoing a process of change. In the process of this change, it is necessary to take care of the environment so that it is still able to support a normal life. One of the ways to provide knowledge is by holding socialization activities for environmental conservation in Kadokan Village. Environmental conservation has many positive impacts on the environment, including being free of air pollution, getting clean water and being healthier and more comfortable in carrying out daily activities for the people of Kadokan Village. The method used is counseling which aims to increase public awareness of the importance of environmental conservation to ensure safety, health, and human survival, especially in Kadokan Village.